Foreign Direct Investments in Southeast Asia - Fredrik Sjöholm (Lund University, School of Economics and Management, Department of Economics, 2013)
Foreign direct investment has been of large importance in economic growth and global economic integration over the last decades. South East Asia has been part of this development with rapidly increasing inflows of FDI. However, there are large variations over time and between countries in the region as regard to the policies towards FDI, and in actual inflows of FDI. This chapter aims at examining the size of FDI in South East Asia and the trends in it. The main determinants of FDI in Southeast Asia as well as their effect on the host countries are also discussed and examined.
Keywords: F21; F23; O53; 330; Foreign direct investment; multinational firms; Southeast Asia; economic development